2006
DOI: 10.1007/s00586-006-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience in cell-based therapeutics: intervention and outcome

Abstract: Disc herniation treated by discectomy results in a significant loss of nucleus material and disc height. Biological restoration through the use of autologous disc chondrocyte transplantation (ADCT) offers a potential to achieve functional integration of disc metabolism and mechanics. Nucleus regeneration using autologous cultured disc-derived chondrocytes has been demonstrated in a canine model and in clinical pilot studies. In 2002 a prospective, controlled, randomized, multicentre study comparing safety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 26 publications
2
157
0
1
Order By: Relevance
“…1,2,10,16,20,22,25,[30][31][32][34][35][36][37][38]46,48,49,53,54,56,57,60,62,[64][65][66][67]69,73,83,90 The EuroDISC study, by Meisel and colleagues, 49 investigated the percutaneous transplantation of autologous disc chondrocytes. Following microdiscectomy, disc chondrocytes were harvested and expanded in vitro and were subsequently injected into the NP 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,10,16,20,22,25,[30][31][32][34][35][36][37][38]46,48,49,53,54,56,57,60,62,[64][65][66][67]69,73,83,90 The EuroDISC study, by Meisel and colleagues, 49 investigated the percutaneous transplantation of autologous disc chondrocytes. Following microdiscectomy, disc chondrocytes were harvested and expanded in vitro and were subsequently injected into the NP 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have used mesenchymal stem cells (MSCs) and the chondrocyte-like cells derived from the nucleus pulposus (NP) of the disc or juvenile articular cartilage to repair the intervertebral disc. 1,2,7,[13][14][15][22][23][24][25][26][27][28][29][30]38,39,57,59,74,75 Unlike disc chondrocytes, MSCs can be readily isolated from a variety of tissues including bone marrow, adipose tissue, and synovium. 9,76 Moreover, MSCs possess the capacity for self-renewal and thus maintain their undifferentiated phenotype in multiple subcultures, but when they are exposed to the appropriate stimuli, they can undergo differentiation into cells of the mesenchymal lineage, such as chondrocytes, osteocytes, and adipose cells.…”
mentioning
confidence: 99%
“…In another clinical trial, patients who received injection of autologous disc cell transplantation showed less reduction in fluid content compared with the control group and better pain relief at 24 months (77). Autologous disc cell transplantation is currently the only therapeutic technique that has been clinically tested in intervertebral disc degeneration and shows longterm clinical outcomes (77).…”
Section: Cell Replacementmentioning
confidence: 99%